Comparison of direct and sandwich type immunoassays on electrospun nanofibers using of metal organic frameworks as a fluorescence probe - Kirbay, Fatma Ozturk; Yazgan, Idris; Demirkol, Dilek Odaci (Elsevier BV, 2022)
Here, colloidal fluorescent Fe (III) metal organic frameworks (FeMOFs) were synthesized using FeCl3 as Fe3+ ion source and lactose 1-aminonaphthalene (L1AN) as an organic linker by one-step synthesis approach. C-reactive protein antibody (Anti-CRP) was conjugated to L1AN-FeMOF through amide bond formation, which was then applied to the detection of C-reactive protein (CRP) using sandwich-type and immunometric assays. To cover 96-well plate surfaces, polycaprolactone and poly (amic acid) (PCL/PAA) electrospun nanofibers were synthesized. Limit of detection (LOD) for CRP was obtained as 4.8 pg/mL for the sandwich assay and 9.0 pg/mL for the immunometric assay in buffer systems using high throughput sensing approach. Real sample applications in artificial saliva and simulated serum validated the reliability of the approach. Selectivity control tests were performed using common serum-based interferents, for which minimum to no interference was observed. Based on the findings, the developed assay can be offered as a new approach in the detection of CRP in clinical samples. © 2022 Elsevier B.V.

This study is supported by Ege University Scientific Research Projects Coordination Unit (Project Number: FOA-2021-22714 . Fatma Öztürk Kirbay thanks to YÖK ( Council of Higher Education ) 100/2000 scholarship program (Sensor Technologies) and 2211-A TUBITAK National Scholarship Program for PhD Students 2018/3.

Ege Üniversitesi: FOA-2021-22714; Yükseköğretim Kurulu
Keywords: Synthesised; Metal organic frameworks; Nanofibers; Chemical detection; Iron compounds; C-reactive proteins; Fluorescence; C-reactive protein; Metalorganic frameworks (MOFs); Ion sources; Electrospun nanofibers; Fe 3+; Organometallics; Proteins; Nanobiotechnology; Immunometric assay; Amides; Chlorine compounds; aminonaphthalene; Sandwich type assay; Sandwich types; Fluorescence probes; 4. Education; 3. Good health